Surviving with a resident despot: do revegetated patches act as refuges from the effects of the noisy miner (Manorina melanocephala) in a highly fragmented landscape?. Issue 7 (28th April 2016) - Mortelliti, Alessio; Ikin, Karen; Tulloch, Ayesha I.T.; Cunningham, Ross; Stein, John; Michael, Damian; Lindenmayer, David B.
Abstract: Aim: To provide, through a large‐scale long‐term field study, an empirical evaluation of the extent to which revegetated patches act as refuges for woodland bird species in the face of enhanced abundance of a native despotic species in a highly fragmented landscape. Location: South‐west slopes, New South Wales, Australia. Methods: Birds were surveyed using point counts over a 9‐year period. Colonization/extinction dynamics of local bird populations were modelled using multiple‐season occupancy models. Results: We show how the spread of the noisy miner ( Manorina melanocephala ), an indirect effect of habitat loss and fragmentation, is now the main driver of bird distribution patterns, affecting 65% of the studied species, including 10 species of conservation concern. Noisy miners both increased the risk that birds would become extinct in patches and prevented birds colonizing new patches. We discovered that restoration plantings, despite having low noisy miner abundance, rarely acted as a refuge for bird species: only 6 of 42 species, and only one of conservation concern, showed a positive response to plantings. Instead, bird species colonized or persisted more in regrowth or old growth sites where the abundance of the noisy miner was relatively low. Main conclusions: Despite a major restoration effort of replanted vegetation over several decades, the majority of our target bird species preferred native woodland patches over plantings, and particularly native patches with a low abundance of the noisy miner. Our study showed that conservation actions such as habitat restoration aimed at reversing the effects of habitat loss and fragmentation should be preceded by a careful threat‐mitigation prioritization considering, in particular, the indirect effects of fragmentation, such as the impact of despotic or invasive species. Our results support calls to manage noisy miners by undertaking actions that will reduce their numbers, such as through culling.